P790 Determining the origins of repeat trichomonas vaginalis infections using clinical versus genotype-informed criteria. (14th July 2019) - Kissinger, Patricia; Bradic, Martina; Muzny, Christina; Mena, Leandro; Lillis, Rebecca; Schwebke, Jane; Beauchamps, Laura; Taylor, Stephanie; Schmidt, Norine; Augostini, Peter; Secor, William; Carlton, Jane; et al.
Abstract : Background: High rates of repeat T. vaginalis infections post-treatment have been reported. It is essential to understand the origin of these infections (i.e. treatment failure or reinfection) to determine the best secondary prevention measures. Self-reported sexual behavior and medication adherence can be subject to bias. The purpose of this study is to examine the origins of early repeat T. vaginalis infections in women using clinical versus genotype-informed criteria. Methods: Women with T. vaginalis confirmed by culture or nucleic acid amplification test (NAAT), who were randomized to receive 2 g or 7-day 500 mg BID metronidazole (MTZ), were retested 3–12 weeks post treatment at test-of-cure (TOC). Viable isolates from women who were TOC TV+ were genotyped (baseline and TOC isolates) and MTZ susceptibility (TOC only) was evaluated. Sexual and treatment adherence histories were elicited by computer-assisted self-administered survey. Treatment failure was defined using two criteria: 1) clinical (a combination of MTZ adherent per self-report+ no follow-up sexual exposure per self-report + no MTZ resistance), and 2) genotype-informed (concordant baseline and TOC genotype with no follow-up sexual exposure per self-report). Results: Of 80 repeat positives, 78 were evaluated using clinical and 49 using genotype-informed criteria. Per clinical criteria, 87.2% were treatment failure, 7.7% were reinfection and 5.1% were new infection. Per genotype-informed criteria, 51.0% were treatment failure, 10.2% were reinfection and 38.3% were new infection. In subset analysis, comparing the 49 with both clinical and genotype-informed assessments, 61.2% agreed and 38.8% disagreed (kappa 0.29 indicating poor reliability). Of 44 women who denied having a new partner during follow-up, 14 (31.8%) had a discordant genotype. Conclusion: Using either criteria, most TOC T. vaginalis positives were treatment failure rather than re-infections. Clinical and genotype-informed classification were not well correlated. Possible explanations for this will be discussed. Disclosure: No significant relationships.